THEMATIC PROGRESSION ANALYSIS IN EFL POSTGRADUATE STUDENTS’ THESIS ABSTRACTS - Zakia Habsari; Emi Emilia (Tell-us Journal)
Coherence is one of aspects that plays significant role in writing. Coherence can be analysed using the Thematic Progression of The Theme system of systemic functional linguistics. However, there is lack of study on analysing thematic progression of postgraduate students’ thesis abstracts. The study aimed at investigating thematic progression pattern in thesis abstracts written by postgraduate students in a university in Bandung. A descriptive qualitative design was employed in this study since it attempts to describe and analyse the textual data. Six thesis abstracts of postgraduate students in a state university in Bandung were collected from the university website. The result shows that three thematic progression patterns: Theme Reiteration, Zig-zag, and Multiple-Rheme pattern, were realized in their thesis abstracts. The most used thematic progression pattern in students’ thesis abstracts is the Zig-Zag pattern (59.38%). However, students may have difficulties in writing abstracts since they are not using various patterns and the limitation of words in abstract. Besides, students still need guidance in writing an appropriate abstract for their thesis.